Survey on chronic disabling low back pain among care workers at nursing care facilities: a multicenter collaborative cross-sectional study - Yoshimoto T; Oka H; Fujii T; Kawamata K; Kokaze A; Koyama Y; Matsudaira K (Journal of Pain Research, 2019)
Takahiko Yoshimoto,1,2 Hiroyuki Oka,2 Tomoko Fujii,2 Kayo Kawamata,2 Akatsuki Kokaze,1 Yoshiko Koyama,3,4 Ko Matsudaira21Department of Hygiene, Public Health and Preventive Medicine, Showa University School of Medicine, Tokyo, Japan; 2Department of Medical Research and Management for Musculoskeletal Pain, 22nd Century Medical & Research Center, Faculty of Medicine, The University of Tokyo, Tokyo, Japan; 3Department of Physical Therapy, Faculty of Health Sciences, Kinjo University, Ishikawa, Japan; 4Ishikawa Occupational Health Support Center, Ishikawa, JapanPurpose: Care workers at nursing care facilities have high rate of low back pain (LBP). Although increasing evidence has revealed the important role of psychosocial factors in chronic LBP, factors associated with chronic LBP interfering with work have not been fully investigated in Japanese workers at nursing care facilities. The present study aimed to determine the prevalence of chronic LBP interfering with work and related factors of chronic LBP including psychosocial factors, among workers at nursing care facilities.Material and methods: Eligible participants in the present study were Japanese workers at 95 nursing care facilities in Ishikawa Prefecture (n=2,242). Of these, 1,345 participants completed a self-administered questionnaire that included the following items: individual characteristics, severity of LBP, sleep problem, fear-avoidance beliefs (Tampa Scale for Kinesiophobia: TSK), STarT Back Screening Tool (SBST), fatigue, somatizing tendency, and work-related stress such as job satisfaction, job demand, interpersonal stress at work, and social support. The logistic regression analysis was used to assess factors associated with chronic disabling LBP.Results: Of participants who completed the questionnaires, 159 (11.8%) reported chronic LBP that interfered with their work. The multivariable analysis of related-factors of chronic disabling LBP found statistically significant associations with the following: high score of psychological subscale in SBST (adjusted odds ratio [aOR]: 5.83, 95% confidence interval [CI]: 3.55–9.59), high score of TSK (aOR: 1.08, 95% CI: 1.05–1.13), and high somatizing tendency (aOR: 2.07, 95% CI: 1.31–3.23).Conclusion: Psychological factors, including fear-avoidance beliefs or somatizing tendency, showed significant association with chronic LBP that interfered with work, among workers at nursing care facilities. Our results suggest that these factors would need to be considered in addition to screening for the risk factors of LBP chronicity by SBST when evaluating workers with chronic disabling LBP.Keywords: low back pain, care worker, nursing care facility, psychological factor, fear-avoidance, somatizing tendency